2017
DOI: 10.1111/jfs.12387
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Enterobacteriaceae from traditional Serbian cheese and their physiological characteristics

Abstract: In this paper, the presence of enterobacteria in autochthonous cheese from Southeast Serbia (Sokobanja), made in the traditional way, was investigated. The samples from different households, was taken during the summer and the autumn. Chemical and physical characteristics of samples (water content, fat content, acidity, pH, and sodium chloride content) were examined. In the analyzed samples of cheese, four different genera of family Enterobacteriaceae (Klebsiella [65%],, and Enterobacter [5%]) were identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…The processes of cheese-making, sampling, and the storage of cheese samples were described in detail in Mladenović, Muruzović, Zugić Petrović, Stefanović, and Comić (2017). The tested cheese was produced in countryside households around Sokobanja (Southeastern Serbia), in traditional way.…”
Section: Cheese-making Sampling and Storagementioning
confidence: 99%
“…The processes of cheese-making, sampling, and the storage of cheese samples were described in detail in Mladenović, Muruzović, Zugić Petrović, Stefanović, and Comić (2017). The tested cheese was produced in countryside households around Sokobanja (Southeastern Serbia), in traditional way.…”
Section: Cheese-making Sampling and Storagementioning
confidence: 99%
“…According to the results described in Mladenović et al (2018) and Muruzović et al (2018), all tested indicator stains demonstrated sensitivity to streptomycin and chloramphenicol. P. mirabilis ATCC 12,453 showed resistance to tetracycline (10 mm…”
Section: Antimicrobial Potentialmentioning
confidence: 73%
“…For comparison, indicator stains were tested on the sensitivity to the antibiotic, and this method was described in detail Mladenović et al () and Muruzović et al ().…”
Section: Methodsmentioning
confidence: 99%
“…E. coli ATCC 25922 was used as a positive control. The bacteria were previously isolated from Serbian cheese (Sokobanja region) and determined at the Laboratory for Microbiology at the Faculty of Science, University of Kragujevac (KGPMF) (MLADENOVIĆ et al, 2018). The collection of identified bacterial species was kept in a 20% glycerol/medium mixture at -80 °C.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%